Impact Of Socıo-Economıc Indıcators And Polıcy Interventıon On Infant Mortalıty Rate: Evıdence From States And Uts Of Indıa - Harsh Bardhan (International Journal of Advanced Science and Technology, 2020)
The article aims to examine the impact of social & economic indicator such as Total Fertility Rate (TFR), Female Literacy Rate (FLR), Female Employment Rate (FER), Gross State Domestic Product (GSDP) and policy intervention which is measured by expenditure on Integrated Child Development Scheme (ICDS) on Infant Mortality Rate (IMR) in India. The data of the 35 states and UT were collected from national survey and a multiple regression was run followed by F test and p test to find the factors which significantly affected the IMR. The analysis showed that at 95% confidence level TFR and FLR significantly affected the IMR. There is reduction of IMR with increase in GSDP but this impact is not significant at 95% confidence level. A positive correlation is found between FER and IMR but this is not significant at our confidence level. The IMR showed a negative correlation with FLR and a positive correlation with TFR. The most dominant factor which affected IMR was observed to be TFR. The research supports the existing literature on the effect of TFR and FLR on IMR. The article also concludes that social sector expenditure measured by expenditure on ICDS has no significant impact on IMR which is concerning as this shows that government is not doing enough to curtail IMR and hence government needs to improve its policy interventions. Keywords: IMR, Female Literacy Rate, Total Fertility Rate, ICDS, Policy implementation, women empowerment.